IMPLEMENTASI TEKNIK STEGANOGRAFI MENGGUNAKAN METODE ADAPTIVE MINIMUM ERROR LEAST SIGNIFICANT BIT REPLACEMENT (AMELSBR) - Astria Hijriani; Wamiliana Wamiliana; Pandya Panditatwa (Jurnal Komputasi, 2014)
Security is an important aspect in digital data transmission, and steganography is one way for hiding a secret message in such a way so that others are not aware of the existence of something in the message. In this research, we built a digital steganography system using web-based with Adaptive Minimum - Error Least Significant Bit Replacement (AMELSBR) method. The media to hide the message is on the form of .jpg, the output is on the form of .png, and the message is on the form of .txt. The procedures for applying AMELSBR method are Capacity Evaluation, Minimum - Error Replacement and Error Diffusion. The result shows that the AMELSBR method is able to manage for hiding and restoring files without causing excessive distortion (noise) in stego image. The AMELSBR method has a possibility of returning most files to image manipulation such as the change of image Brightness and Contrast with the black color dominant (rgb(0,0,0)), white color dominant (rgb(255,255,255)).